The Influence of Leadership Style, Work Motivation, and Work Environment on Employee Performance in the Yogyakarta City Civil Service Police Unit - Genoveva Harrtanti; Eko Prasojo (Hemispheres Press, 2026)
This study aims to determine the effect of leadership style, work motivation, and work environment on employee performance at the Yogyakarta Municipal Civil Service Police Unit (Satpol PP). This research employed a quantitative method with a survey approach. The population consisted of 123 employees of Satpol PP Yogyakarta City. The sampling technique used was saturated sampling, in which all members of the population were selected as research samples. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). Data analysis was conducted using SPSS version 27 software The results showed that leadership style had a positive and significant effect on employee performance with a significance value of 0.001. Work motivation had a positive and significant effect on employee performance with a t-value of 4.605 and a significance level of less than 0.05. Work environment had a positive and significant effect on employee performance with a t-value of 4.783 and a significance level of less than 0.05. Simultaneously, leadership style, work motivation, and work environment had a positive and significant effect on employee performance with an F-value of 164.716 and a significance level of less than 0.05. The coefficient of determination test showed an Adjusted R Square value of 0.801, indicating that 80.1% of employee performance variation could be explained by leadership style, work motivation, and work environment, while the remaining 19.9% was influenced by other factors outside the scope of this study.